Identification of therapeutic drugs with high drug sensitivity for brain metastasis-associated tumor cells (MBMATCs) and high-brain metastasis (MBM) index patients. - Jingxin Zeng (18773484) (2025)
(A-I) Differential drug-response analysis (boxplots) and Spearman’s correlation analysis (right panel) for Mirin_1048, PR-4708671_1129 and XAV939_1268. (TIF)